Tomografia computadorizada para avaliação pulmonar e hepática da espécie Ara ararauna - SILVA, Ieverton Cleiton Correia da (2022)
The aim of this study was to describe the aspects of pulmonary and hepatic tomographic anatomy associated with the quantitative assessment of the pulmonary and hepatic radiodensity of Blue-and-Yellow macaws (Ara ararauna). Birds of the genus Ara are part of the Psittacidae family including macaws, parakeets and parrots, being the largest representatives of this family. Among the main pathologies found in birds of genus Ara, diseases of pulmonary and hepatic origin are the most prominent. Their lungs are well inserted in the chest wall and do not have great expansion and its liver is divided into 2 lobes: right and left hepatic lobe, being divided by the interlobar notch in most species. Quantitative computed tomography (QCT) can be defined as a CT technique to measure HU radiodensity of body tissues. This technique can be used for the diagnosis and monitoring of patients with diseases that alter the density of the liver and lung parenchyma. The first study aims to perform a tomographic description of the normal pulmonary parenchyma of free-living Blue-and-Yellow macaws (Ara ararauna), in addition to providing information regarding lung volume and degree of normal radiographic attenuation of the lung parenchyma, obtaining average values of -727,19±44,53 HU using the histogram technique and -722,19 ± 29,69 HU by the ROI technique with no statistical differences between them. And the second study aimed to determine the normal value of radiographic attenuation of the liver parenchyma of Blue-and-Yellow macaws (Ara ararauna), using QCT, obtaining the results of means of hepatic radiographic attenuation ranging from 53,73 HU a 54,44 HU. From these results it was possible to determine the normal values for radiographic attenuation of the pulmonary and hepatic parenchyma of Blue-and-Yellow macaws, providing relevant information for literature and possible further studies related to the differentiation of pathologies involving the lungs and liver of these birds.